직장에서 성충이 검출된 수입성 구충(鉤蟲) 감염 1례 - 용태순(Tai-Soon Yong); 신호준(Ho-Joon Shin); 임경일(Kyung-il Im); 김원호(Won-Ho Kim) (Korean journal of parasitology, 1992)
An imported case of rectal hookworm infection was diagnosed by stool examination and recovery of adult worms from the rectal mucosa by sigmoidoscopy. The chief complaints of a patient were diarrhea, abdominal pain and weight loss for about 1 month after returning from his travel abroad to the Southeast Asia. Leukocytosis ($16, 750/μ\ell$) and peripheral eosinophilia (33.7%) were noticed without anemia. Typical hookworm eggs were detected by stool examination, and 3 worms were collected by sigmoidoscopy from rectal mucosa of this patient. Those worms were confirmed as adult worms of Ancylostoma duodenale(♂:1, ♀: 2) based on their morphological characteristics. The symptoms were relieved after treatment with anthelmintics. This case was considered as one of the imported parasitic infections in Korea, and a rare case of hookworm infection on human rectal mucosa. 동남아시아를 여행하고 귀국한 후부터 시작된 약 1개월 동안의 복통, 설사 및 체중 감소를 주소로 내원한 서울이 거주지인 32세의 남자 환자가 구충증으로 진단되었다. 혈액 검사상 백혈구 수(16,750개111) 및 호산구의 백분율(33.7%)이 모두 상승되어 있었으나 빈혈 소견은 없었다. 대변 검사상 전형적인 구충의 충란이 대량 발견되었으며, S상결장경검사시 직장에서 적출된 충체 3마리를 관찰한 결과, 기생 부위가 전형적이지는 않았으나, 구강 및 생식기 등의 형태학적인 특징을 고려하여 듀비니구충(Ancylestoma duodenale)의 성충(♂: 1, ♀: 2마리)으로 동정 할 수 있었다. 구충제 (aetendazole)를 투여한 후 상기한 모든 증상이 급속히 호전되었다. 해외 여행시 감염되어 국내에 수입된 기생충 감염의 한 중례로 생각되며, 인체의 대장에 이소기생 (이소기생)한 구충 감염을 직접 확인한 드문 경우로 생각된다.